Body mass index and gestational weight gain in two selected Medical Officer of Health areas in the Gampaha District - C Abeysena; P Jayawardana (College of Community Physicians of Sri Lanka, 2011)
Objective: To describe gestational weight gain pattern according to the body mass index (BMI) categories. Methods: This is a descriptive study conducted in two Medical Officer of Health areas of the Gampaha District. Pregnant women were recruited on or before 16 weeks of gestation and followed up until delivery. Maternal weight was measured at the booking visit, during the second trimester and at delivery. Inadequate and excessive weight gain were defined as weight gain below and above the Institute of Medicine (IOM) 2009 recommendations for the BMI categories as well as Ministry of Health (MoH) recommendations. Results: Two hundred and forty seven (30%) of the women were underweight, 432(52%) were normal weight and 131(18%) overweight and obese. According to the Asian BMI classification, 338(41 %) were normal weight and 225(29%) were overweight and obese. Total mean weight gain for the sample was 10.6(SD 3.3) kg and mean rate of gestational weight gain was 0.27(SD 0.08) kg/week. Mean weight gain during second trimester was 6.7(SD 2.7) kg and during third trimester 3.9(SD 2.2) kg. Mean gestational weight gain and rate of weight gain per week was higher among underweight women. Of the 710, 404(57%) women gained less and 62(8.7%) more weight, than recommended by the IOM, whereas 108(15%) gained more weight by MoH standards. Conclusions: One third of the women were underweight and mean gestational weight gain and rate of weight gain per week were higher amongst them. More than half of the women gained less weight than recommended. Key Words: Body mass index; gestation; pregnancy; weight gain DOI: http://dx.doi.org/10.4038/jccpsl.v16i1.3869   Journal of the College of Community Physicians of Sri Lanka Vol.16(1) 2011, p30-34